Pattern Visually Evoked Potentials in Japanese Girl With Optic Neuritis and Seropositive to Anti-myelin Oligodendrocyte Glycoprotein (MOG) Antibody - Takano, Shunichiro; Hanabusa, Aya; Yoshikawa, Yuji; Sassa, Kaori; Shimura, Airi; Shoji, Takuhei; Ohde, Hisao; Shinoda, Kei; Yamanouchi, Hideo (Frontiers in Neurology, 2019)
Purpose: To describe a Japanese girl with unilateral optic neuritis (ON) who was seropositive for the anti-myelin-oligodendrocyte glycoprotein (MOG) antibody. Serial recordings of the pattern visual evoked potentials (pVEPs) were made to follow the dynamic changes of the disease activity. Observations: A 5-year-old girl developed a sudden reduction of vision and deep ocular pain in her right eye. On examination at our university hospital, the best-corrected visual acuity (BCVA) was light perception, and a swelling of the optic disc and tortuous vessels at posterior pole were observed in the right eye. MRI demonstrated her right optic nerve was hyperintense on short TI inversion recovery (STIR) sequence. A diagnosis of right papillitis was made, and she was treated with steroid pulse therapy followed by gradually tapered oral prednisolone. The visual acuity decreased to no light perception and plasmapheresis combined with high-dose intravenous immunoglobulin therapy was performed. The decimal visual acuity rapidly improved and recovered to 1.2 and no recurrence was observed for at least one year. On day 19, she was found to be anti-MOG antibody positive and anti-AQ4 antibody negative. pVEPs were recorded during the course of the disease process which showed the dynamic changes of the physiology of the visual pathways. The implicit times of the N75 and P100 components were prolonged in the right eye in the acute phase. The right visual acuity remained at 1.2 for at least one year, but the implicit times of the N75 and P100 components of the pVEPs of the right eye were still prolonged compared to left eye. Conclusion: Our findings support the relationship between the anti-MOG antibodies positivity and the prolonged pVEPs. Further analyses of the pVEPs and other clinical findings of the optic neuritis are needed to establish the clinical significance of the anti-MOG antibodies positivity and optic neuritis for the diagnosis, treatment, and prognosis for this disease.